Minimum wages and employment in China - Tony Fang; Carl Lin (IZA Journal of Labor Policy, 2015)
Since China promulgated new minimum wage regulations in 2004, the frequency and magnitude of changes in minimum wages have been substantial. This paper uses county-level minimum wage data combined with urban household survey micro-dataset from 16 representative provinces as a merged county-level panel to estimate the employment effects of minimum wage changes in China over the 2002-2009 period. In contrast to the mixed results reported by previous studies using provincial-level data, we present evidence that minimum wage changes led to significant adverse effects on employment in the Eastern and Central regions of China, and resulted in disemployment for females, young adults, and low-skilled workers.
Keywords: J38; 330; Minimum wage; China; Employment close